Reflections on International Institute on Peace Education 2013: Exploring a Possible World Free from Violence - Cannon, Susan (In Factis Pax: Journal of Peace Education and Social Justice, 2014)
Transformative researchers and practitioners from all over the globe use conceptions of critical thinking that are—at heart—the same. Further, they see such thinking as a tool to change the world for the better. Brazilian education reformer Paulo Freire (1970/2000) sees critical reflection and committed social action in a deeply intertwined cycle arising from questioning and rethinking knowledge. American Nel Noddings’s (2007) definition encompasses reasoned analysis of issues, as well as reflection on moral and social beliefs and action. Tanzanian-born Ladislaus Semali (2004) offers perspectives from elders in his native Chaggaland, who describe critical thinking as imanya, (“to know intellectually and to be morally or spiritually motivated”) and kusare (“to consider all the possibilities ... think deeply”). He concludes, “Critical thinking is a lived activity, not an abstract academic pastime” (pp. 170-171).